The Actors Involved in the Career Scripts of Young People: Actantial Analysis - Janne Varjo; Mira Kalalahti (Nordic Journal of Transitions, Careers and Guidance)
The aim with this paper is to scrutinise the career scripts of young people in Finland by the means of actantial analysis. We examined the actantial structures of narratives on career scripts in Finland with 31 follow-up interviews. The premise of this paper is drawn from careership theory. The aim is to contribute theoretically and empirically to the qualitative body of knowledge on career scripts of young people, and the various actantial positions involved. Actantial analysis offers a novel and undiscovered way to portray in practice the ways in which career scripts are simultaneously built on structural, interpersonal, and intrapersonal factors. Abstrakti Artikkelissa tarkastelemme aktatiaalisen analyysin avulla nuorten uraskriptejä Suomessa. Analysoimme tutkimusaineistona toimivan 31 haastatteluparin avulla suomalaisten uraskriptien aktistiaalisia rakenteita. Tavoitteenamme on edistää teoreettisesti ja empiirisesti nuorten uraskriptejä – ja niihin kytketyviä aktanttipositioita – koskevaa ymmärrystä. Aktantiaalinen analyysi tarjoaa teoreettisesti perustellun tavan kuvata tapoja, joilla uraskriptit rakentuvat samanaikaisesti rakenteellisille, yksilöiden välisille ja henkilökohtaisille tekijöille. Avainsanat: Aktantiaaliset rakenteet; Uraskriptit; Koulutussiirtymät